Digging Deeper: Engaging in Reflexivity in Interpretivist-Constructivist and Critical Leisure Research. (1st July 2021) - Duffy, Lauren N.; Fernandez, Mariela; Sène-Harper, Aby
Abstract: As interpretivist-constructivist and critical scholarship has advanced within leisure science, so too does the need for more comprehensive approaches for reflexivity. Reflexivity, which can be described as an act, capacity, or practice to self-critique one's own biases that may influence the construction of knowledge, is an important means for meeting standards of goodness or quality within qualitative research. This study sought to strengthen leisure research through a conceptual exploration of reflexivity. The authors created a series of vignettes to analyze their past research experiences, employing hermeneutics and feminist epistemologies to guide reflexive practice. Consequently, social and relational context of knowledge, representation and voice, positionality and embodiment, awareness of politico-ideological character, and unconscious/emotional entanglement emerged as dimensions of a reflexive framework. Informed by this process, a collection of questions are offered as a tool to assist others with more holistic reflexive practice within the leisure sciences.